Development and in vitro assessment of a bi-layered chitosan-nano-hydroxyapatite osteochondral scaffold. (15th April 2022) - Pitrolino, Katherine A.; Felfel, Reda M.; Pellizzeri, Laura Macri; M Laren, Jane; Popov, Alexander A.; Sottile, Virginie; Scotchford, Colin A.; Scammell, Brigitte E.; Roberts, George A.F.; Grant, David M.
Abstract: An innovative approach was developed to engineer a multi-layered chitosan scaffold for osteochondral defect repair. A combination of freeze drying and porogen-leaching out methods produced a porous, bioresorbable scaffold with a distinct gradient of pore size (mean = 160–275 μm). Incorporation of 70 wt% nano-hydroxyapatite (nHA) provided additional strength to the bone-like layer. The scaffold showed instantaneous mechanical recovery under compressive loading and did not delaminate under tensile loading. The scaffold supported the attachment and proliferation of human mesenchymal stem cells (MSCs), with typical adherent cell morphology found on the bone layer compared to a rounded cell morphology on the chondrogenic layer. Osteogenic and chondrogenic differentiation of MSCs preferentially occurred in selected layers of the scaffold in vitro, driven by the distinct pore gradient and material composition. This scaffold is a suitable candidate for minimally invasive arthroscopic delivery in the clinic with potential to regenerate damaged cartilage and bone. Graphical abstract: Unlabelled Image